A SOCIOLOGICAL EXPLORATION OF LANGUAGE LECTURERS' JOURNEY INTO AFRICAN LANGUAGE TEACHING - Adedokun, Theophilus Adedayo; Usadolo, Sam Erevbenagie; Awung, Felix Nkwatta (Faculty of Administrative Science, Universitas Brawijaya, 2024)
This qualitative study explores the experiences of selected lecturers of African languages in South Africa. Through in-depth interviews, the study reveals that apartheid-era segregation shaped early dispositions towards language teaching, while multilingual upbringings sparked interest in African languages, though colonial policies suppressed their use in schools. While post-apartheid policies have promoted the use, teaching and learning of African languages in higher education, lecturers of these languages still face the challenge of lack of institutional support and the unavailability of resources. Using a Bourdieusian theoretical lens, the study shows how broader discourses around language, identity and power manifest in lecturers’ efforts to revalue African language education. Lecturer’s habitus was shaped by familial, sociopolitical and educational contexts orienting them toward language teaching. Furthermore, strategic accumulation of cultural capital through credentials enabled progression into academia. By leveraging social capital via professional networks, they accessed information and advocacy to become lecturers. Within the competitive field of academia, they continuously strove for more prestigious positions and capital. To counter institutional barriers, lecturers have collaborated with language communities to develop localized pedagogies validating indigenous cultures. A key finding is that technology access enabled lecturers to effectively perform roles, publish research, and accumulate capital to advance professionally over time. This study gives voice to lecturers’ multifaceted experiences teaching African languages in South African universities. The findings further provide insights to guide policies and practices supporting marginalized language teaching.